2018
DOI: 10.3847/1538-4357/aaec78
|View full text |Cite
|
Sign up to set email alerts
|

Seeding the Formation of Mercurys: An Iron-sensitive Bouncing Barrier in Disk Magnetic Fields

Abstract: The inner part of protoplanetary disks can be threaded by strong magnetic fields. In laboratory levitation experiments, we study how magnetic fields up to 7 mT influence the aggregation of dust by observing the self-consistent collisional evolution of particle ensembles. As dust samples we use mixtures of iron and quartz in different ratios. Without magnetic fields, particles in all samples grow into a bouncing barrier. These aggregates reversibly form larger clusters in the presence of magnetic fields. The si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 57 publications
0
39
1
Order By: Relevance
“…The red line shows a fit curve for the planets (ρ = 4100r −0.21 ). Britt and Consolmagno (2003); Lewis (1972); Stacey (2005); heliocentric distances of chondrite parent bodies are from Desch et al (2018Desch et al ( ) et al 2013Kruss and Wurm 2018). We highlight electromagnetic separation of magnetized micro-particles of Fe-Ni alloys (existing below their Curie point with a stable magnetic spin) from silicates (Harris and Tozer 1967;Larimer and Anders 1970) coupled with metal-oxide separation during chondrule formation as being effective segregation processes (e.g., Connolly Jr. et al ( 2001)).…”
Section: Processes In the Protoplanetary Diskmentioning
confidence: 84%
See 2 more Smart Citations
“…The red line shows a fit curve for the planets (ρ = 4100r −0.21 ). Britt and Consolmagno (2003); Lewis (1972); Stacey (2005); heliocentric distances of chondrite parent bodies are from Desch et al (2018Desch et al ( ) et al 2013Kruss and Wurm 2018). We highlight electromagnetic separation of magnetized micro-particles of Fe-Ni alloys (existing below their Curie point with a stable magnetic spin) from silicates (Harris and Tozer 1967;Larimer and Anders 1970) coupled with metal-oxide separation during chondrule formation as being effective segregation processes (e.g., Connolly Jr. et al ( 2001)).…”
Section: Processes In the Protoplanetary Diskmentioning
confidence: 84%
“…10 AU, the putative initial formation location for WIS 91600, ungrouped C2 chondrite) reported by Bryson et al (2020). Kruss and Wurm (2018) suggested that enhanced growth of iron-rich dust aggregates in the inner region of protoplanetary disks leads to an iron gradient in the solar system. A corollary of this model is that planetary migration in the inner solar system did not disrupt this final result and that the Fe content can help us determine where and when an object was dominantly formed.…”
Section: Processes In the Protoplanetary Diskmentioning
confidence: 84%
See 1 more Smart Citation
“…Kruss and Wurm [138] just recently carried out first collision experiments with levitated aggregates consisting of a mix of iron and silicates placed in a magnetic field. While magnetic erosion has not been verified so far, another interesting observation was made.…”
Section: Magnetic Aggregationmentioning
confidence: 99%
“…2mm 2mm Figure 10. Formation of an elongated cluster of aggregates after applying a magnetic field of 7 mT (from Kruss and Wurm [138]). This mechanism can clearly shift the bouncing barrier to larger sizes, preferentially for metal (iron) rich aggregates.…”
Section: Magnetic Aggregationmentioning
confidence: 99%